Sex Differences in Healthspan Predict Lifespan in the 3xTg-AD Mouse Model of Alzheimer’s Disease - Kane, Alice E.; Shin, Sooyoun; Wong, Aimee A.; Fertan, Emre; Faustova, Natalia S.; Howlett, Susan E.; Brown, Richard E. (Frontiers in Aging Neuroscience, 2018)
Mouse models of Alzheimer’s Disease (AD) exhibit marked differences in life expectancy depending on their genotype and sex. The assessment of frailty could provide a measure of healthspan to facilitate comparisons between different AD models. We used a validated mouse frailty index (FI) assessment tool to explore genotype and sex differences in lifespan and healthspan of 3xTg-AD mice and their B6129F2 wild-type controls. This tool is based on an approach commonly used in people and quantifies frailty by counting the accumulation of age-related health deficits. The number of deficits in an individual divided by the total number measured yields an FI score theoretically between 0 and 1, with higher scores denoting more frailty. Male 3xTg-AD mice aged 300-600 days had higher FI scores (Mean FI=0.21 ± 0.03) than either male wild-type (Mean FI=0.15 ± 0.01) or female 3xTg-AD mice (Mean FI=0.10 ± 0.01), and the elevated frailty scores were accompanied by parallel increases in mortality. Frailty increased exponentially with age, and higher rates of deficit accumulation elevated mortality risk in all groups of mice. When mice were stratified by FI score, frailty predicted mortality, at least in females. Therefore the mouse clinical FI provides a valuable tool for evaluating healthspan in mouse models of AD with different lifespans.